Effect of fair value accounting on the company’s reputation - Riahi, Olfa; Khoufi, Walid (International Journal of Accounting and Economics Studies, 2016)
The purpose of this paper is to study in the French context the impact of the application of fair value on the shareholder value creation by comparing the information’s relevance of accounting indicators of French corporate groups in the industrial sector included in the CAC All-Tradable between pre-fair value period (2001-2003) and the post-fair value (2005-2007). Using the method of logistic regression permits us to demonstrate, firstly, that the variables of traditional character still retain their rank as key indicators determining stock return whatever the accounting principle relating thereto, and we noticed, on the other hand, that there is a marked improvement in information content of variables if and only they were submitted as understandable and uncomplicated under the model of fair value.